Alcohol consumption and consequences in adolescents in 68 low and middle-income countries – a multi-country comparison of risks by sex. (1st December 2019) - Leung, Janni; Chiu, Vivian; Connor, Jason P.; Peacock, Amy; Kelly, Adrian B.; Hall, Wayne; Chan, Gary C.K.
Highlights: First to present country & regional sex differences in alcohol in LMIC adolescents. There are large variations by location; males were not always at higher risks. Female alcohol drinking rates and consequences close to males in some countries. Lack of up-to-date data to inform estimates in some LMICs – crucial call for data. Interactive data visualization tools are provided. Abstract: Aims: Alcohol use is a leading risk factor for disease burden among youth. This study estimated sex differences in the prevalence of alcohol use and consequences among adolescents living in low and middle-income countries (LMIC). Design: Multi-staged cross-sectional international standardized self-report questionnaires administered in the classroom. Setting: The Global school-based student health survey (GSHS) comprised adolescents from 68 LMIC between 2003–2014. Participants: 271, 156 students aged 13–17 years old. Measurements: Alcohol measures included: past month alcohol consumption, history of intoxication and alcohol-related problems. Regions were based on the World Health Organization definitions: Africa, America, Eastern Mediterranean, Europe, South-east Asia, and Western Pacific. Findings: Overall, males had higher odds of alcohol use (OR = 2.38 [1.91–2.96]), a history of intoxication (OR = 2.64 [2.11–3.31]), and alcohol-related problems (OR = 1.72 [1.41–2.10]) than females. All regions recorded overall greater odds of alcohol use by males versus females; five regions (excluding Europe) recorded greater odds of intoxication in males; and three regions (America, South-east Asia, and Western Pacific) recorded greater odds of alcohol-related problems amongst males. However, there were country-level differences – in some countries, adolescent drinking rates and consequences were comparable by sex. Countries with the highest odds of alcohol use among males compared to females were Indonesia, Myanmar, Cambodia, Tuvalu, Morocco, Senegal, Kiribati, and Thailand. Conclusions: Among adolescents living in LMIC, males had on average two-fold higher odds of drinking alcohol and experiencing adverse consequences. Growing affluence and improvements in sex equality in societies may increase the future prevalence of hazardous drinking in females in LMICs.